CFD analysis of PBI and PSF membranes with MWCNT for water recovery from brackish water RO reject by FO and validation with experimental results - Venkatesh, S. S.; Pandiyarajan, V.; Velraj, R.; Sundararajan, T. (Frontiers in Energy Research, 2025)
As global water scarcity intensifies, sustainable alternatives to reverse osmosis (RO), which is an energy-intensive process, are essential, especially given the environmental risks posed by wastewater and brackish water discharge. This study explores forward osmosis (FO) as a viable alternative, using 2M MgCl2 as the draw solution (DS) and brackish water RO reject as the feed solution (FS). In the present work, a computational fluid dynamics (CFD) study is performed to model water transport through FO membranes using two thin-film flat sheet membranes—polysulfone (PSF) and polybenzimidazole (PBI)—enhanced with MWCNT additives, aiming to recover water from brackish water RO reject. This type of CFD evaluation of MWCNT-modified FO membranes is a unique aspect of the present work. A non-Darcy porous medium model was applied in CFD to simulate flow through the FS, DS, and the membrane, with pressure drop correlated to the osmotic pressure gradient. The PBI/MWCNT2 wt% membrane achieved the best overall performance with a CFD-predicted WF of 31.5 L/m2.hr or LMH, closely aligning with the experimental value of 31.2 ± 0.4 LMH. The CFD results for all the membranes are also in close agreement with the experimental data, confirming the accuracy of the model. The WF in the PBI and PBI/MWCNT membranes has a greater effect than the PSF and PSF/MWCNT membranes due to its affinity for water, the π–π bonds between PBI and MWCNT, and the interaction of nitrogen atoms on its imidazole ring with water, forming hydrogen bonds.